Power and inaction: why organizations fail to address workplace bullying. Issue 3 (23rd August 2020) - Hodgins, Margaret; MacCurtain, Sarah; Mannix-McNamara, Patricia
Abstract : Purpose: Bullying affects at least one-third of the workers through either direct exposure or witnessing, both of which lead to compromised health, and as a result, reduced organizational effectiveness or productivity. However, there is very little evidence that organisations provide effective protection from bullying, and in fact, the converse appears to the case. The purpose of this paper to explore the role of both individual and organisational power in the creation and maintenance of the problem. Such an approach moves away from the specific practice of identifying "bullying" that typically engages targets and perpetrators in a dance that is really just around the edges (Sullivan, 2008) of a larger problem; a culture that permits the abuse of power and ill-treatment of workers, in both practices and through organisational politics. Design/methodology/approach: This paper elucidates key problems with organisational response as identified in the literature and critically examines weak organisational response to workplace bullying using the power theory, arguing that while overt approaches to addressing bullying appear to be underpinned by a simplistic, functionalist understanding of power, practices on the ground are better explained by more sophisticated "second-dimension" theorists. Findings: There is a need for organisations to move beyond the current individualistic understanding of bullying towards a more nuanced understanding of how anti-bullying policies and procedures are themselves an exercise in institutional power protecting and reinforcing dominant power structures. Research limitations/implications: The literature from which this paper is drawn is limited to studies published in English. Practical implications: The authors advocate a realistic assessment of the role of both individual and organisational power in the creation and maintenance of workplace bullying, as a way forward to plan appropriate intervention. Social implications: Workplace bullying is problematic for organisations at several levels, and therefore for society. Originality/value: That power is relevant to workplace bullying has been apparent since the work of Brodsky in 1976 and Einarsen's early work, this paper builds on a the more nuanced work of McKay (2014), D'Cruz and Noronha (2009), Liefooghe and MacDavey's (2010) and Hutchinson et al. (2010), exploring the organisational response to the raising of bullying issues by individual employees as an exercise of power.